(Either) a practical grammatical study in the Holy Quran: "Section II" - Mohamed, Sebah H. (Humanities Journal of University of Zakho, 2017)
The Conjunctions "horoful ma'aany", which refers to some semantic tool consider to semantic matters in Arabic linguistics and rehotritic studies, play prominent role in the performance of the intended meanings. This study concern about one of them which is ('immah) that is used frequently in Arabic texts, especially the traditional ones. It is an exhaustive study in this tool, bares the essence of it that scholars and linguists have not taken so much interest in it. Therefore, the study defines it, demonstrate its types and forms, and the frequency of it in the Holly Quran. This has been done in accordance with a pattern based on description, induction, contrasting and criticism. Corroborating all this and referring all thoughts and poetic verses to their owners as much as possible and according to the requirements of scientific methods. Finally, the research found out several results, the most highlighted ones are: Repetition of mistakes in many issues for the subsequentes transfer of the formers without scrutiny, thus, referring of thoughts to their owners is not accurate to the owners in this subject. - Despite not mentioning the various narrations related to the topic, many of poetic verses related to this tool ('immah) have not been referred to their authors. Also they have not been mentioned in both encyclopedias and dictionaries of poetic related to these kind of topics although they have been stated in some witnessed the fame among specialists.